STRUCTURA TAXONOMICĂ A COMUNITĂŢILOR DE ALGE DIN SOLURILE OCUPATE CU CULTURA DE POBUMB DIN MOLDOVA - Trofim, Alina; Donțu, Natalia; Melniciuc, Cristina (CEP USM, 2011)
Edaphic algae are the main components of agricultural ecosystems. They are the bio-indicators of soil quality.During the two years was studied taxonomic structure and eco-biomorphic spectrum of algal communities in twelve corn fields from four localities from different parts of country. Have been identified 31 species and intra-specific varieties of alga. Most diverse proved to be blue – green alga. Comparative analysis of soil’s algalflora in different regions of the country, shows a high diversity of soil’s algalflora from south areas of Moldova.
Keywords: alge edafice; algele cianofite filamentoase